Dancing on Paper: Finger Painting for Fine Motor Skill Development in Early Childhood - Devina Areta Cahyaningrum; Suharti; Mallevi Agustin Ningrum; Dhian Gowinda Luh Safitri; Kartika Rinakit Adhe; Budi Purwoko (Jurnal Paedagogy, 2026)
This study aims to explore the process of fine motor development in early childhood through the “Dancing on Paper” intervention, focusing on how participation in the activity supports the development of fine motor skills within an early childhood education setting. Employing a qualitative single-case study design, this research examines changes in children’s physical dexterity and coordination through a structured multi-day artistic intervention. Data were collected from five selected participants to observe key indicators of fine motor skills, including finger muscle strength, hand–eye coordination, and movement flexibility. The collected data were analyzed using qualitative thematic analysis through the stages of data reduction, data display, and conclusion drawing. The results indicate that participation in finger painting activities enhances children’s ability to control fine muscle movements and supports their readiness for subsequent academic tasks, such as writing. The findings suggest that the sensory-rich characteristics of the “Dancing on Paper” activity provide effective stimulation for early childhood fine motor development. This study contributes to early childhood education practices by highlighting creative arts activities as an effective pedagogical strategy for supporting children’s physical development.